2022
DOI: 10.1542/peds.2022-058878
|View full text |Cite
|
Sign up to set email alerts
|

Helmet Use in Preventing Head Injuries in Bicycling, Snow Sports, and Other Recreational Activities and Sports

Abstract: Bicycling, snow sports, and other recreational activities and sports are important activities to keep children and youth active as part of a healthy lifestyle. These activities can be associated with serious and fatal head and facial injuries. Helmets, when worn correctly, are effective in decreasing head injuries and fatalities related to these activities. Legislation for helmet use is effective in increasing helmet use in children and, ultimately, in decreasing deaths and head and facial injuries. A multipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
2
2
0
Order By: Relevance
“…However, even with stable helmet use rates, given the increasing numbers of children engaging in AWHUR, there was an increase in the gross number of head injuries and patients presenting without a helmet at the time of injury. In evaluating these head injuries and helmet usage, our data align with previous research finding that helmets reduce the severity of TBI (Lee et al 2022 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, even with stable helmet use rates, given the increasing numbers of children engaging in AWHUR, there was an increase in the gross number of head injuries and patients presenting without a helmet at the time of injury. In evaluating these head injuries and helmet usage, our data align with previous research finding that helmets reduce the severity of TBI (Lee et al 2022 ).…”
Section: Discussionsupporting
confidence: 87%
“…Although most patients presented with a GCS of 13 to 15 during the 3-year time period (96%), there was an alarming trend toward an increase in children with a GCS of less than 8 from 2.5% pre-pandemic to 3.3% during the pandemic, although this was not statistically significant. Additionally, finding that approximately 7% of children presenting unhelmeted had a GCS of 12 or less compared to 0.9% of helmeted patients again aligns with our knowledge that helmets can reduce severe brain injury (Lee et al 2022 ; Gulack et al 2015 ). While a wide variety of factors can influence neurosurgical consultation and it may be influenced by local practice, it is also important to note the increase in neurosurgical consultation from 6.5% in 2018 to 17.7% of patients in 2020.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Children appear to be overrepresented and at greater risk than adults [ 4 , 5 ]. Both epidemiological and biomechanical studies have demonstrated the efficacy of helmets in reducing the incidences and severity of head injuries [ 2 , 6 10 ]. In some countries, children are legally required to wear helmets [ 1 ].…”
Section: Introductionmentioning
confidence: 99%